Metagenomic small molecule discovery methods - Charlop-Powers, Zachary (2014)
Metagenomic approaches to natural product discovery provide the means of harvesting bioactive small molecules synthesized by environmental bacteria without the requirement of first culturing these organisms. Advances in sequencing technologies and general metagenomic methods are beginning to provide the tools necessary to unlock the unexplored biosynthetic potential encoded by the genomes of uncultured environmental bacteria. Here, we highlight recent advances in sequence- and functional- based metagenomic approaches that promise to facilitate antibiotic discovery from diverse environmental microbiomes.